EMISI ENERGI DAN KEBIJAKAN KENDARAAN LISTRIK: STUDI KOMPARASI ANTARA CHINA DAN INDONESIA - Al Qodri, Muhammad Iqbal; Widyastutik (Pusat Studi Pembangunan Pertanian dan Pedesaan (PSP3), 2023)
China and Indonesia are countries with large populations and contributors to world carbon dioxide emissions. One step to reduce emissions is through the adoption of electric vehicle policies. The penetration rate of electric vehicles in China and Indonesia can differ due to the policy approach used. In this study, the analysis method is a bilateral comparative study with a literature review. Based on the results of the analysis, China has adopted an electric vehicle policy since 2001 accompanied by sustainable programs and incentives. Meanwhile, Indonesia has only focused on electric vehicles, especially battery-based electric motor vehicles since 2019. Through the market approach (demand and supply) and infrastructure approach, different policy conditions in China and Indonesia are obtained, and can be used as a benchmark for decision-making for the Indonesian government. The policy implications of the analysis are increasing monetary and non-monetary incentives for producers and consumers, increasing local government participation, and clarifying the steps to execute Indonesia's electric vehicle roadmap.